Editorial: Warm Welcome - Satish Prasad Barnawal (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
An elderly male presents to orthopedic clinic with severe back pain for fifteen days. He is unable to sit or stand. The pain remains persistent even while lying supine. He also complains of nausea, anorexia and cough with blood tinged sputum since ten days. He gives past history of grade II benign prostatic  hyperplasia with nodule under prostate specific antigen monitoring. Examination reveals no significant finding.  The clinical features literally points to nowhere. Blood counts, electrolytes, renal function test, liver function test, acid phosphatase, LDH, sputum for acid fast bacilli, sputum culture, Bence Jones Protein and Serum Electrophoresis are found to be within normal limit.